Satisfiability of general intruder constraints with and without a set constructor. (May 2017) - Avanesov, Tigran; Chevalier, Yannick; Rusinowitch, Michael; Turuani, Mathieu
Abstract: Many decision problems on security protocols can be reduced to solving deduction constraints expressing whether an instance of a given message pattern can be constructed by the intruder. Most constraint solving procedures for protocol security rely on two properties of constraint systems called monotonicity and variable-origination . In this work we relax these restrictions by giving a decision procedure for solving general intruder constraints (that do not have these properties) that stays in NP. The result is also valid modulo an associative, commutative and idempotent theory. The procedure can be applied to verify security protocols in presence of multiple intruders.